Forecasting the sectoral GVA of a small Spanish region - Lampis, Federico (Economics and Business Letters, 2016)
Our main goal in this paper is to evaluate the point forecasting accuracy of several time series econometric models when applied to a small Spanish region. The variable of interest is the sectoral GVA of the Basque Country. The results support the use of univariate models, such as ARMA and SETAR, which outperform the causal model in forecasting accuracy. The use of a causal model, such as the Transfer Function model, does not offer a systematic advantage, even if it makes use of the regional statistical information available for the Basque Country.